Variability and trends of carbon parameters at a time series in the eastern tropical Atlantic. Issue 1 (1st December 2016) - Lefèvre, Nathalie; Veleda, Doris; Araujo, Moacyr; Caniaux, Guy
Abstract : Hourly f CO2 is recorded at a time series at the PIRATA buoy located at 6°S 10°W in the eastern tropical Atlantic since June 2006. This site is located south and west of the seasonal Atlantic cold tongue and is affected by its propagation from June to September. Using an alkalinity–salinity relationship determined for the eastern tropical Atlantic and the observed f CO2, pH and the inorganic carbon concentration are calculated. The time series is investigated to explore the intraseasonal, seasonal and interannual timescales for these parameters, and to detect any long-term trends. At intraseasonal timescales, f CO2 and pH are strongly correlated. On seasonal timescales, the correlation still holds between f CO2 and pH and their variations are in agreement with those of sea surface salinity. At interannual timescales, some important differences appear in 2011–2012: lower f CO2 and fluxes are observed from September to December 2011 and are explained by higher advection of salty waters at the mooring, in agreement with the wind. In early 2012, the anomaly is still present and associated with lower sea surface temperatures. No significant long-term trend is detected over the period 2006–2013 on CO2 and any other physical parameter. However, as atmospheric f CO2 is increasing over time, the outgassing of CO2 is reduced over the period 2006–2013 as the flux is mainly controlled by the difference of f CO2 between the ocean and the atmosphere. A longer time series is required to determine if any significant trend exists in this region.